2014
DOI: 10.1210/jc.2014-1154
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label, Prospective Pilot Clinical Study of Denosumab for Severe Hyperparathyroidism in Patients With Low Bone Mass Undergoing Dialysis

Abstract: Denosumab is effective in restoring bone mass and reducing bone pain in patients on dialysis with secondary hyperparathyroidism. It also allows for a more aggressive use of calcitriol to control hyperparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 19 publications
1
57
0
5
Order By: Relevance
“…In contrast, most patients in the previously reported cases were not receiving sufficient VD treatment either before or after DMAb administration (Talreja 2012;McCormick et al 2012;Torregrosa 2013;Agarwal et al 2013;Ungprasert et al 2013;Farinola and Kanjanapan 2013). Furthermore, clinical studies by Chen et al (2014Chen et al ( , 2015 indicated that hypocalcemia was corrected shortly after adjusting Ca intake, VD dosage and Ca dialysate in HD patients with SHPT. Therefore, we consider that DMAb-induced hypocalcemia can be prevented with uptitration of the VD dosage and Ca supplementation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In contrast, most patients in the previously reported cases were not receiving sufficient VD treatment either before or after DMAb administration (Talreja 2012;McCormick et al 2012;Torregrosa 2013;Agarwal et al 2013;Ungprasert et al 2013;Farinola and Kanjanapan 2013). Furthermore, clinical studies by Chen et al (2014Chen et al ( , 2015 indicated that hypocalcemia was corrected shortly after adjusting Ca intake, VD dosage and Ca dialysate in HD patients with SHPT. Therefore, we consider that DMAb-induced hypocalcemia can be prevented with uptitration of the VD dosage and Ca supplementation.…”
Section: Discussionmentioning
confidence: 93%
“…Next, we address the hypocalcemia induced by DMAb in patients with CKD. Previous studies reported that hypocalcemia was the most common adverse effect of DMAb (Jamal et al 2011;Chen et al 2014). In addition, recent studies showed that treatment with DMAb induced severe hypocalcemia in CKD patients (particularly, CKD stage 4-5D patients complicated with SHPT) compared to the general population (Jamal et al 2010;Dave et al 2015).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Показан хороший эффект Деносумаба в сочетании с кальцитриолом у диализных паци-ентов с тяжелым вторичным ГПТ и выраженным дефицитом минеральной костной массы [47,48]. В Японии появилось первое сообщение об успеш-ном применении Деносумаба у реципиента почеч-ного трансплантата с тяжелым рецидивирующим ГПТ, несколько раз подвергшегося хирургическим вмешательствам.…”
Section: другие лекарственные средстваunclassified